On a Certain Identification Method for Stand Simulation Tests - Gierulski, W.; Sender, Z. (Engineering Transactions, 1991)
In the paper the identification method, called the averaging method, is presented. Information on the tested object is obtained from a number of experiments made under similar conditions. The possibility of applying this method in stand simulation tests securing the conditions for the necessary experiments is pointed out. The method of forming the input signals for simulation tests appropriate for the presented identification method is described. An example of synthesis the input signals in the tests of a singlebucket excavator, real experiments being replaced with the computer ones, is discussed.